Design, Synthesis and molecular docking study of hybrids of quinazolin-4(3H)-one as anticancer agents - Sukanya Nara; Achaiah Garlapati (Ars Pharmaceutica)
ABSTRACT A series of 4-(2-(4-substituted phenyl)-4-oxoquinazolin-3(4H)-yl)-N-(2-(4-fluorophenyl)-4-oxo-5-(arylidene)thiazolidin-3-yl) benzamides (VIa-n) have been synthesized by condensation of N-(2-(4-fluorophenyl)-4-oxothiazolidin-3-yl)-4-(4-oxo-2-(4-substituted phenyl)quinazolin-3(4H)-yl)benzamides (Va-b) with various aryl/heteroaryl aldehydes using conventional methodology. All compounds were screened for their in vitro anticancer activity against the human breast cancer cell lines (MCF-7), human lung cancer cell lines (A549) using MTT assay method and doxorubicin is used as standard drug. Compound VId, VIk and VIn showed high potency against A549 cell lines with IC50 values 0.035±0.002 µM, 0.031±0.002 µM and 0.030±0.002 µM respectively compared to 0.023±0.002 µM showed by the standard. However, highest activity against MCF-7 cell lines was exhibited by Va, Vb, VIk and VIn with IC50 values between 0.040 - 0.050 µM. All the remaining compounds showed moderate anticancer activity against both the MCF-7 and A549 cell lines. To understand the interactions with active binding site of receptor, molecular docking study was also performed.